Research on the seam performance of waterproof clothing based on continuous ultrasonic welding technology. Issue 2 (18th April 2016) - Shi, Hui; Wang, Jianping; Chen, Xiaona; Luo, Shunhua; Zhang, Lingxi
Abstract : Purpose: – The purpose of this paper is to develop an improved waterproof seam production technology (ultrasonic welding-thermo adhesive tape sealing (USW-TATS)). The technology will improve the waterproof performance of seam which has problem resulted from needle holes and thread like seam leaking and excess shrinkage. Design/methodology/approach: – Threadless seams were produced by ultrasonic welding (USW) with coated and lamination fabric to replace the traditional sewing process in sewing-thermo adhesive tape sealing (S-TATS). The process efficiency was evaluated by methods-time measurement. Seam performance including hydrostatic pressure, shrinkage and tear force was compared among three technologies (USW, USW-TATS and S-TATS). The effect of USW parameters (amplitude, roller pressure and roller speed) on the USW-TATS seam performance was investigated. SEM analysis was carried out to examine the condition and morphology of the joints cross-section. Findings: – It was found that waterproof performance and dimensional stability of USW-TATS seam were superior to that of S-TATS seam. Tear force and hydrostatic pressure increased first and then decreased with the increasing of USW parameters in UAW-TATS process. Binary regression relationships were found between the USW parameters and tear force or hydrostatic pressure. Shrinkage decreased with the increasing of roller pressure and speed. Practical implications: – Research results can be applied to predict seam performance of waterproof clothing, reduce equipment parameters setting time and enhance product quality in industry. Originality/value: – A threadless production technology (USW-TATS) was proposed to improve waterproof performance and dimensional stability of outdoor clothing seams.